The new general sistem of royalties sistem could affect the departament of Cesar (2016)
Through this paper we intend to show the new parameters of the General System of Royalties SGR at the time of allocation of resources in order to establish a parallel between the new system and the previous and get results that demonstrate the effects that changing these systems have resulted in the country's departments as currently the allocation of these resources is based on the approval of projects to benefit the different sectors in the community, especially in the department of Cesar as this was one of benefited the most from the previous system for its high coal production.